ChemInform Abstract: Chemistry of Halonitroethenes. Part 3. Reinvestigation of the Nitration of Trichloroethene — Subsequent Reactions of the Products and Evaluation of Their Antimicrobial and Antifungal Activity. Issue 16 (March 2016) - Zapol'skii, Viktor A.; Namyslo, Jan C.; Sergeev, Galina; Broenstrup, Mark; Gjikaj, Mimoza; Kaufmann, Dieter E.
Abstract: The nitration reaction of trichloroethene to its three main products is comprehensively investigated and optimized.